التسويق الالكتروني الخيار الاستراتيجي الأنسب لتطوير المؤسسات الناشئة - صديق, ليندة; لفايدة, عبد الله (جامعة الوادي - University of Eloued, 2023)
تواجه المؤسسات الناشئة العديد من التحديات التسويقية التي تضطرها إلى تجنيد مواردها على النحو الأمثل وإلى إستخدام طرق جديدة ومبتكرة للوصول إلى الزبائن وإقناعهم؛ ومن هنا يبدو التسويق الإلكتروني خيار إستراتيجي لا بد منه بالنسبة لهذه المؤسسات لما يمنحه من حلول تسويقية رقمية للتعريف بها وبمنتجاتها، وتهدف هذه الدراسة إلى التعرف على التسويق الالكتروني ودوره في تحقيق النمو والنجاح للمؤسسات الناشئة، وقد توصلت إلى جملة من النتائج أهمها أن التسويق الإلكتروني يسمح للمؤسسة الناشئة بالتفاعل اللحظي مع الزبائن ومنه بالحصول على معلومات تمكنها من تعديل عناصر عرضها التسويقي وإتمام عملية التبادل بنجاح حيث تظهر خيار ات التسويق بالمحتوى والتسويق عبر مواقع التواصل الاجتماعي بالإضافة إلى التسويق عبر محركات البحث كاستراتيجيات تسويقية مناسبة لحملات تسويق المؤسسات الناشئة من حيث التكلفة والنتائج. ct: Emerging enterprisesor or as named Start-ups face many marketing challenges that force them to optimally recruit their resources and use new and innovative ways to reach and persuade customers. Hence, e-marketing appears as a necessary strategic option for these institutions, as it provides digital marketing solutions to introduce them and their products. This study aims to identify e-marketing and its role in achieving the growth and success of start-ups, and it has reached a number of results, the most important of them is that e-marketing allows the emerging enterprise to interact in real time with customers, and from it to obtain information that enables it to modify the elements of its marketing offer and complete the exchange process successfully Content marketing, social media marketing, and search engine marketing options are emerging as suitable marketing strategies for startup marketing campaigns in terms of cost and results.
Digital marketing the most appropriate strategic choice for the development of emerging enterprises
مقال
Keywords: المؤسسات الناشئة ; التسويق الإلكتروني ; ممارسات التسويق الإلكتروني; ds: Emerging institutions, e-marketing, e-marketing practi